An evaluation of the psychometric properties of the Indicator of Relative Need (IoRN) instrument. Issue 1 (December 2016) - Canny, Anne; Robertson, Frances; Knight, Peter; Redpath, Adam; Witham, Miles
Abstract Background The Indicator of Relative Need (IoRN) instrument is designed for both health and social care services to measure function and dependency in older people. To date, the tool has not undergone assessment of validity. We report two studies aimed to evaluate psychometric properties of the IoRN. Methods The first study recruited patients receiving social care at discharge from hospital, those rehabilitating in intermediate care, and those in a rehabilitation at home service. Participants were assessed using the IoRN by a single researcher and by the clinical team at baseline and 8 weeks. Comparator instruments (Barthel ADL, Nottingham Extended ADL and Townsend Disability Scale) were also administered. Overall change in ability was assessed with a 7 point Likert scale at 8 weeks. The second study analysed linked routinely collected, health and social care data (including IoRN scores) to assess the relationship between IoRN category and death, hospitalisation and care home admission as a test of external validity. Results Ninety participants were included in the first study, mean age 77.9 (SD 12.0). Cronbach's alpha for IoRN subscales was high (0.87 to 0.93); subscales showed moderate correlation with comparator tools (r  = 0.43 to 0.63). Cohen's weighted kappa showed moderate agreement between researcher and clinician IoRN category (0.49 to 0.53). Two-way intraclass correlation coefficients for IoRN subscales in participants reporting no change in ability were high (0.88 to 0.98) suggesting good stability; responsiveness coefficients in participants reporting overall change were equal to or better than comparator tools. 1712 patients were included in the second study, mean age 81.0 years (SD 7.7). Adjusted hazard ratios for death, care home admission and hospitalisation in the most dependent category compared to the least dependent IoRN category were 5.9 (95 % CI 2.0–17.0); 7.2 (95 % CI 4.4–12.0); 1.1 (95 % CI 0.5–2.6) respectively. The mean number of allocated hours of care 6 months after assessment was higher in the most dependent group compared to the least dependent group (5.6 vs 1.4 h, p  = 0.005). Conclusions Findings from these analyses support the use of the IoRN across a range of clinical environments although some limitations are highlighted.